Neighbourhood planning and the right to the city: confronting neoliberal state urban practices in Salvador, Brazil. Issue 1 (2nd January 2018) - Manzi, Maya; Figueiredo, Glória Cecília dos Santos; Mourad, Laila Nazem; Rebouças, Thaís de Miranda
ABSTRACT: In this article, we discuss the possibilities for and challenges to the urban planning process at the neighbourhood level, from the perspective of the right to the city. We focus on the 2 de Julho, a neighbourhood located in the Old Centre of Salvador, Bahia (Brazil), where processes of gentrification have pressed the local population to demand its own neighbourhood plan. We problematise neighbourhood planning from the radical perspective of the right to the city, in its potential to generate a collaborative process that originates 'in-conflict' and as an instrument of negotiation vis-a-vis the state. We argue that neighbourhood planning not only promotes autonomy and self-management, but also contributes to making the State more accountable. In this way, it has the potential to subvert conventional urban practices that reproduce socio-spatial exclusion, inequalities and injustices whilst contesting the neoliberal logic that dispenses the state from its social responsibilities.